The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cells10061377
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer with Bone Metastasis: Molecular Insights and Clinical Management

Abstract: Despite the remarkable advances in the diagnosis and treatment of breast cancer patients, the presence or development of metastasis remains an incurable condition. Bone is one of the most frequent sites of distant dissemination and negatively impacts on patient’s survival and overall frailty. The interplay between tumor cells and the bone microenvironment induces bone destruction and tumor progression. To date, the clinical management of bone metastatic breast cancer encompasses anti-tumor systemic therapies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 108 publications
1
37
0
Order By: Relevance
“…In vivo experiment, 2 mice in the control group started to have grasping weakness 10 days after tumor formation, which is also in line with the characteristics of nerve infiltration and metastasis in the early stage of ACC ( 27 ). The results showed that the dysfunction rate was significantly reduced after RPS3 knockdown.…”
Section: Discussionsupporting
confidence: 64%
“…In vivo experiment, 2 mice in the control group started to have grasping weakness 10 days after tumor formation, which is also in line with the characteristics of nerve infiltration and metastasis in the early stage of ACC ( 27 ). The results showed that the dysfunction rate was significantly reduced after RPS3 knockdown.…”
Section: Discussionsupporting
confidence: 64%
“…However, young metastatic BC patients might have better prognosis than elderly patients ( 6 ). BC most often metastasizes to the bone, which not only negatively affects the quality of life of patients, but also affects the longevity of patients ( 7 ). Although the diagnosis and treatment of BC has made great progress, bone metastasis is still a significant challenge for clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the PI3K/Akt/mTOR pathway is the most commonly upregulated pathway in HR-and HER2+ breast cancers, being involved in many aspects of cell growth, proliferation, survival, metabolism, and immune response regulation [40]. A deep disturbance of these processes is caused by abnormal activating events targeting PI3K/Akt, which leads to tumorigenesis, metastasis, tumor progression, and therapy resistance [36,[41][42][43]. In addition, PTEN activity in the nucleus is critical for tumor suppression due to the modulation of the DNA damage response and anti-tumor immune activity, independently of PTEN phosphatase activity [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%